Degradation, classification, and management of soils from alluvial‐gold mine spoils in the Southeastern Peruvian Amazon - Velásquez Ramírez, M. G.; Nazario Rios, J. C.; Gobin, A.; Pillaca, M.; Thomas, Evert; Guerrero Barrantes, J. A.; Román, U.; Becerra Lira, E.; Muñoz Ushñahua, A.; Nascimento Herbay, P.; Rodriguez Achata, L.; Garate-Quispe, J.; et al. (Wiley, 2025)
ABSTRACT Artisanal and Small‐Scale Gold Mining (ASGM) carried out by individual miners or small enterprises with limited capital, significantly contribute to land degradation and loss of biodiversity‐rich forests in the Amazon. Due to limited information on the edaphic conditions crucial for restoring these degraded areas, a soil evaluation method was employed in representative locations of the Peruvian Amazon, including two native communities and one protected natural area. The categorization of ASGM‐degraded areas into cultural landscape units was confirmed and validated. Sentinel‐2 and UAV remote sensing revealed over 122,000 ha of deforestation since the 1980s. Surface and soil profile assessments identified extreme new soil conditions with low chemical and physical fertility, characterized by coarse texture and rock fragments, which hinder revegetation, especially during prolonged dry seasons. These degraded soils were classified as Entisols and Technosols according to Soil Taxonomy and the World Reference Base. Over time, natural regeneration and plantations improved soil formation, aligning with recognized soil classification systems. Under current management practices, restoration planning should prioritize selected shrub and tree species, and consider soil amendments to initiate soil recovery. This approach aligns with self‐sustaining successional stages and contributes to the objectives of Land Degradation Neutrality, Appropriate Mitigation and Adaptation Actions, and Sustainable Development Goals.